LINEAR CONJUGATION PROBLEM WITH MULTIPOINT NONLOCAL CONDITION FOR A PARABOLIC-HYPERBOLIC EQUATION IN CYLINDRICAL DOMAIN - Savka, I. Ya.; Shevchyk, R. V.; Tymkiv, I. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
The linear conjugation problem with multipoint nonlocal condition in the time variable for a mixed parabolic-hyperbolic equation of the second order in a cylindrical domain, which is Cartesian product of the time segment and the spatial multidimensional torus, is investigated. The conditions of the existence and uniqueness of а solution to the problem in the scale of Sobolev spaces are obtained. It has been proved that these conditions fulfill for almost all (with respect to the Lebesgue measure) values of the left node of the multipoint condition.